ANALISIS KERAGAMAN GENETIK TANAMAN JARAK PAGAR LOKAL (JATROPHA CURCAS L.) BERDASARKAN PENANDA MOLEKULER RANDOM AMPLIFIED POLYMORPHIC DNA - Maftuchah . (Jurnal Gamma, 2009)
DNA based RAPD (random amplified polymorphic DNA) markers have been used extensivelyto study genetic relationships in a number of fruit crops. A wide genetic diversity exists in theJatropha curcas in Indonesia. Three accession of Jatropha curcas were selected to assess geneticrelatedness. Total genomic DNA were extracted and subjected to RAPD analysis using 10 primers.Of these, 27 primers ampified Jetropha curcas genomic DNA . Cluster analysis clearly showed twogroups, the first consisting ..... Jatropha curcas and th second groups consisting ..................